Donation: short notes between Italian Civil Law and EU Private International Law - Passarelli, Gianluigi (CUADERNOS DE DERECHO TRANSNACIONAL, 2015)
The donation in p.i.l. is an old problem in particular for the characterization and the current situation in certain EU Member States. This article briefly analyzes the relationship between the donation with Rome I Regulation and the recent EU Regulation 650/2012. Finally the article focuses on the Italian legal system and describes the problem, elaborating on the different solutions that might be adopted. Key words: Donation, Conflicts of law, Diritto Internazionale Privato, Applicable Law, Rome I Regulation, EU Regulation 650/2012. Riassunto: La donazione nel diritto internazionale privato è un vecchio problema sia per la qualificazione dell’ istituto che per l’ attuale scenario in alcuni Stati europei. L’ articolo si prefigge di analizzare brevemente la relazione che la donazione ha con il Regolamento Roma I e con il recente Regolamento 650/2012. Infine l’ articolo si sofferma sull’ ordinamento giuridico italiano descrivendo le problematiche sottese, cercando di elaborare differenti soluzioni che potrebbero essere adottate. Parole chiave: Donazione, Conflicts of law, EU Private International Law, Legge applicabile, Regolamento Roma I, Regolamento 650/2012.